2016
DOI: 10.1002/clen.201500101
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Tropical Vertical Subsurface Flow Constructed Wetlands at Different Hydraulic Loading Rates

Abstract: The hydraulic loading rate (HLR) plays a vital role in pollutant removal in constructed wetlands. This study evaluated the effects of HLR variation on pollutant removal in continuously fed vertical subsurface flow (VSSF) constructed wetlands in tropical conditions. Three VSSF wetland beds (Length: 1.4 m, Width: 0.5 m and Depth: 0.6 m), filled with 10-20 mm gravel media, were set up in a tropical region. Two beds were planted with a locally available emergent macrophyte narrow-leaf cattail (Typha angustifolia),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…These results indicate that a 20 cm/day HLR would be the appropriate upper limit for the applied HLR for pollutant removal, with the HSSF configuration being more suitable for BOD 5 , TSS, FC, and NO 3 − -N removal. These results were consistent with laboratory-scale studies reported earlier by Weerakoon et al [7] and Weerakoon et al [21]. Table 3 presents the range of applied mass loading rates (MLRs) and mass removal rates (MRRs) obtained for the VSSF and HSSF wetland units for polishing stream water, and Table 4 …”
Section: Pollutant Removalsupporting
confidence: 89%
See 1 more Smart Citation
“…These results indicate that a 20 cm/day HLR would be the appropriate upper limit for the applied HLR for pollutant removal, with the HSSF configuration being more suitable for BOD 5 , TSS, FC, and NO 3 − -N removal. These results were consistent with laboratory-scale studies reported earlier by Weerakoon et al [7] and Weerakoon et al [21]. Table 3 presents the range of applied mass loading rates (MLRs) and mass removal rates (MRRs) obtained for the VSSF and HSSF wetland units for polishing stream water, and Table 4 …”
Section: Pollutant Removalsupporting
confidence: 89%
“…This is because CWs require longer hydraulic retention time (HRT) or lower HLR [21] for substantial reduction of pollutants. Metcalf and Eddy [22] reported that pollutant removal in CWs is more efficient at 4-15 days HRT.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is recommended to evaluate the elimination of CF by increasing THR to favor more removals [65]. The release of antibiotics (such as phytometallophores and phytochelatins) by the roots of plants [83], plant cover, settlement of microorganisms, exposure to abiotic stress conditions such as pH, temperature, and oxygen concentration can play important roles in the reduction of coliforms [84,85]. In addition, many of these factors are interrelated [86][87][88].…”
Section: Fecal Coliformsmentioning
confidence: 99%
“…However, very limited or no denitrification occurs in Vertical Flow systems. Therefore, the optimum combination of various types of constructed wetlands always depends on the target pollutants (Vymazal, 2009;Weerakoon et al, 2016). …”
Section: Constructed Wetlandsmentioning
confidence: 99%